POTENTIAL OF MICROCRYSTALLINE CELLULOSE-G- POLY(ITACONIC ACID) AS ?-TOCOPHEROL CARRIER MATERIAL - Ibrahim, Ikhsan
The definition of a drug according to the FDA (Food and Drug Administration) is a substance used for the mitigation, treatment, and therapy of a disease. In increasing the effectiveness of treatment, drugs need a carrier to produce a controlled delivery systems. Drug carriers that produce a controlled delivery pattern can release the drug in a constant concentration over a long period of time. With this, the drug is used in the long-term and there is no need for repeated drug doses as in conventional drug delivery systems. This study used a microcrystalline cellulose-graft-poly(itaconic acid) (MCC-PIA) and ?-tocopherol drug models were used. The ?-tocopherol used as a model drug in this study has hydrophobic properties so its bioavailability is low. This reduces the effectiveness of ?- tocopherol in the treatment process. Therefore, an ?-tocopherol carrier is needed to increase bioavailability. The backbone of MCC-g-PIA is hydrophilic, while the side chain is hydrophobic. The amphiphilic structure can result in the formation of micelles. In the synthesis of this copolymer, the grafted itaconic acid DPn was varied to 10 and 20. The % grafting values obtained for MCC-g-PIA DPn 10 and 20 were 60.21% and 22.02%. The characterization carried out on MCC-g-PIA was Fourier Transform Infrared Spectroscopy (FTIR), X-Ray Diffraction (XRD), and Particle Size Analyzer (PSA). The success of copolymer synthesis is proven by the presence of a new peak in the infrared absorption band at 1645 cm-1. That peak indicates the presence of a C=O group of itaconic acid grafted onto the main chain of microcrystalline cellulose. In addition, there was a decrease in the % crystallinity index from 24.27 % for the microcrystalline cellulose chain, to 8.96 % and 10.32 % for MCC-g-PIA DPn 10 and 20. The decrease in % crystallinity index indicated the formation of copolymers due to poly(itaconic acid) chains that disrupt the hydrogen bonds in microcrystalline cellulose thereby reducing the % crystallinity index. The process of carrying ?-tocopherol was carried out by forming micelles with DPn 10 and 20 Critical Micelle Concentration (CMC) values of 50 ppm and 150 ppm. The carrier of ?-tocopherol by MCC-g-PIA can be seen from the enlarged micelle size in the presence of ?-tocopherol from the PSA results. The amount of ?-tocopherol carried by MCC-g-PIA DPn 10 and 20 was 1.74 mg and 0.92 mg, respectively.